Analysis of Knowledge and Attitudes of Mothers with Toddlers at Risk of Diarrhea in the Moramo Health Center Working Area South Konawe Regency - Elda Wahid, Wa Ode; Rahmawati, Rahmawati; Supodo, Timbul (Magister Kesehatan Universitas Mandala Waluya, 2023)
Background: The incidence of diarrhea in Indonesia is the second leading cause of death in children under 5 (five) years of age. Data on the number of cases of diarrhea in children in 15 districts and 2 (two) cities in Southeast Sulawesi Province. South Konawe Regency is in second place with the most cases of diarrhea in toddlers, totaling 77 cases. South Konawe Regency has 24 Community Health Center working areas. In the Moramo Community Health Center area, there were 41 cases of diarrhea in 2021. Method: The type of research used in this research is quantitative with an observational method with a Case Control Study Design approach. This research was carried out in August 2022. This research will be carried out in the Moramo Health Center Work Area, South Konawe Regency, Southeast Sulawesi Province. With a sample of 76 respondents. The sampling technique used in this research was Simple Random Sampling. Result: The results of the research are known from the results of the analysis X2Hit 15.221 > Hit 10,344> df=1), ϕ = 0.504. Conclusion: It is hoped that parents, especially mothers who have toddlers, can increase their knowledge about the causes of diarrhea, improve their attitudes to avoid diarrheal disease, especially in toddlers.